Overcoming the lack of human-interaction in Ubiquitous Group Decision Support Systems - Carneiro, João (2014)
The market globalization and the firms internationalization hinders the matching of the top managers agenda. Therefore, creating conditions for meetings in the same space or time is sometimes impossible. In order to enable the decision making in this kind of scenario the Group Decision Support Sys-tems evolved to the so called Ubiquitous Group Decision Support Systems (UbiGDSS). However, although the UbiGDSS solve part of space-time prob-lems, they originated other problems related to the lack of human interaction, such as: to understand how the arguments used can influence each of the deci-sion makers, what is their satisfaction regarding the decision made, and other affective issues such as emotions and mood. Here we propose a theoretical model that is specially designed for agents in order to understand the interac-tions impact on each agent and their satisfaction with the decision made.